A bioelectrical impedance analysis device for monitoring haemoglobin status in dengue patients - Abdul Rahim, Herlina (International Frequency Sensors Association (IFSA), 2008)
The purpose of this study was to validate a single BIA for predicting hemoglobin (Hb) in dengue patients. The BIA technique based on the passing of low-amplitude electrical current less than 1 mA (500 to 800 mA) with frequency 50 kHz. By using multiple regression analysis, reactance, sex, weight and vomiting were found independent determinants of predicting Hb. Hence, this novel approach of BIA technique can provide rapid, non-invasive, and promising method for monitoring and evaluating the status of the DHF patients.